Cross-species single-cell RNA-seq analysis reveals disparate and conserved cardiac and extracardiac inflammatory responses upon heart injury - Eric Cortada; Jun Yao; Yu Xia; Friederike Dündar; Paul Zumbo; Boris Yang; Alfonso Rubio-Navarro; Björn Perder; Miaoyan Qiu; Anthony M. Pettinato; Edwin A. Homan; Lisa Stoll; et al. (Communications Biology)
Abstract The immune system coordinates the response to cardiac injury and controls regenerative and fibrotic scar outcomes in the heart and subsequent chronic low-grade inflammation associated with heart failure. Adult mice and humans lack the ability to fully recover while adult zebrafish spontaneously regenerate after heart injury. Here we profile the inflammatory response to heart cryoinjury in zebrafish and coronary artery ligation in mouse using single cell transcriptomics. We interrogate the extracardiac reaction to cardiomyocyte necrosis to assess the specific peripheral tissue and immune cell reaction to chronic stress. Cardiac macrophages play a critical role in determining tissue homeostasis by healing versus scarring. We identify distinct transcriptional clusters of monocytes/macrophages (mono/Mϕ) in each species and find analogous pairs in zebrafish and mice. However, the reaction to myocardial injury is largely disparate between mice and zebrafish. The dichotomous response to heart damage between the murine and zebrafish mono/Mϕ and/or the presence of distinct zebrafish mono/Mϕ subtypes may underlie the impaired regenerative process in adult mammals and humans. Our study furnishes a direct cross-species comparison of immune responses between regenerative and profibrotic myocardial injury models, providing a useful resource to the fields of regenerative biology and cardiovascular research.